Profiting with Honor: Cicero’s Vision of Leadership - Bragues, George (Journal of business ethics, 2010)
This article attempts to uncover the relevance of Cicero’s thought to present-day management through an analysis of his last philosophical study, On Duties. Applying a methodology grounded in Socratic skepticism, Cicero synthesizes the Stoics and Aristotle to create his own moral theory. From this theory, we derive a Ciceronian set of recommended traits that make up a model business leader. Central to this model is the recognition that there are two lodestars in life, the beneficial and the honorable. The first directs each of us to attend to our personal happiness, and the second to our moral worth. In Cicero’s view, the life of leading sizable associations is what best satisfies this dual imperative. The honor of a business leader is secured by the practice of four virtues: wisdom, justice, greatness of spirit, and seemliness. A leader properly seeks his/her own benefit by recognizing that success comes from the relationships he/she establishes and that he/she are more apt to cultivate these by being virtuous. Cicero is not so naïve as to fail to see that the beneficial and the honorable may come into tension, noting various examples from business to illustrate the dilemma. But he insists a businessperson can be ethical and prosper at the same time once he/she comprehends the social fellowship of humanity.